Islam Masa Periode Khalifah Rasyidah Masa Usman bin Affan dan Ali bin Abi Thalib - Fadilah, Nafidatul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
After the death of the Prophet Muhammad SAW. Islam needs a replacement for him to lead the Muslims. While the Prophet Muhammad SAW. did not leave a will regarding who would replace him after he died. Islamic leaders at that time knew very well that Islam needed a leader, namely a caliph who was chosen through deliberation. Finally, the Prophet's companions were elected as caliphs in the order of Abu Bakr ash-Shiddiq, Umar bin Khattab, Uthman bin Affan, and Ali bin Abi Talib. The determination of the Ottoman manuscripts to exist during the time of Uthman bin Affan and the existence of total unity that exists in the text of the Koran throughout the world with various sects in the world is one form of the success of the caliph Uthman bin Affan which cannot be rivaled by anyone in uniting Muslims. . Political problems during the time of Ali bin Abi Talib eventually brought Islam to the struggle for theology or theology which led to the emergence of three schools of thought. Keywords : Head of State, Caliph Period, Ottoman Manuscripts